Models of Internal and External Oversight of Police Discretion in the Prevention of Abuse of Power A Study at the North Sumatera Regional Police - Andreas Simbolon, Riki; Aspan, Henry; Rafianti, Fitri (International Conference Epicentrum of Economic Global Framework, 2025)
Police discretion constitutes a strategic authority in criminal law enforcement that enables law enforcement officers to act flexibly in situations not fully governed by written law. However, the exercise of discretion that is not counterbalanced by an effective oversight system has the potential to give rise to abuse of power (abuse of power). This study aims to analyze the models of internal and external oversight of police discretion and to evaluate the effectiveness of such oversight mechanisms in preventing abuse of power within the North Sumatera Regional Police (Polda Sumatera Utara). This study employs normative legal research methodology, incorporating statutory, conceptual, and case approaches, supported by primary, secondary, and tertiary legal materials. The findings indicate that the existing oversight model remains partial and has yet to be systematically integrated, thereby creating oversight gaps in the practice of police discretion. Internal oversight is constrained by limitations in independence and enforcement consistency, while external oversight remains weak in terms of authority and follow-up effectiveness. Accordingly, this study proposes an integrative oversight model that combines internal and external oversight within a mutually complementary system framework, grounded in the principles of legality, accountability, and transparency. This model is expected to enhance oversight effectiveness and prevent the occurrence of abuse of power in criminal law enforcement, both at the regional and national levels.